The endocrine pancreas during exercise in people with and without type 1 diabetes: Beyond the beta-cell - McCarthy, Olivia; Schmidt, Signe; Christensen, Merete Bechmann; Bain, Stephen C.; Nørgaard, Kirsten; Bracken, Richard (Frontiers in Endocrinology, 2022)
Although important for digestion and metabolism in repose, the healthy endocrine pancreas also plays a key role in facilitating energy transduction around physical exercise. During exercise, decrements in pancreatic β-cell mediated insulin release opposed by increments in α-cell glucagon secretion stand chief among the hierarchy of glucose-counterregulatory responses to decreasing plasma glucose levels. As a control hub for several major glucose regulatory hormones, the endogenous pancreas is therefore essential in ensuring glucose homeostasis. Type 1 diabetes (T1D) is pathophysiological condition characterised by a destruction of pancreatic β-cells resulting in pronounced aberrations in glucose control. Yet beyond the beta-cell perhaps less considered is the impact of T1D on all other pancreatic endocrine cell responses during exercise and whether they differ to those observed in healthy man. For physicians, understanding how the endocrine pancreas responds to exercise in people with and without T1D may serve as a useful model from which to identify whether there are clinically relevant adaptations that need consideration for glycaemic management. From a physiological perspective, delineating differences or indeed similarities in such responses may help inform appropriate exercise test interpretation and subsequent program prescription. With more complex advances in automated insulin delivery (AID) systems and emerging data on exercise algorithms, a timely update is warranted in our understanding of the endogenous endocrine pancreatic responses to physical exercise in people with and without T1D. By placing our focus here, we may be able to offer a nexus of better understanding between the clinical and engineering importance of AIDs requirements during physical exercise.